(untitled) (Namibian Journal of Linguistics, Literature and Communication Studies, 2025)
Students use artificial intelligence (AI) generative writing tools to complete writing assignments, regardless of whether such tools are allowed or not. The quality of writing produced by AI tools is superior to that of many university students in terms of grammatical correctness, reduced spelling errors, increased average word length, expanded vocabulary, varied sentence structure, decreased word repetition, and increased punctuation usage. This re-search suggests ways in which AI generative writing tools can be used to improve student writing. It discusses how to make students better editors, so they can improve ChatGPT’s output or tailor it to specific needs. It also provides insights on how to make students better fact checkers, so that they can eliminate hallucinations that AI writing tools generate. These errors of fact make the AI writing tools far less valuable than they would be otherwise. Our work highlights the need to focus writing exercises across the curriculum more on editing and fact checking. We provide numerous insights into programs such as ChatGPT to help instructors without a technical background identify, understand, and process student writing generated by such programs in an improved fashion. We identify several tricks that students use to disguise writing produced by ChatGPT.